The Effectiveness of Instruments and Norms of Physical Ability Tests for Athletes Aged 13-18 Years in East Nusa Tenggara Province - Ronald Dwi Ardian Fufu; Lukas Maria Boleng; Michael Johannes Hadiwijaya Louk; Al Ihzan Tajuddin; Salmon Runesi; Fera Ratna Dewi Siagian (UNIB Press, 2023)
The purpose of this study was to determine the effectiveness of the instrument and the norms for testing the physical ability of athletes aged 13-18 years. This type of research is descriptive research with survey techniques using the test method. The population in this study were Student Education and Training Center athletes in East Nusa Tenggara Province, totaling 69 athletes consisting of 41 boys and 28 girls. The sampling technique used in this study is nonprobability sampling of 69 athletes. The instruments used in this study were the 400 meter running test, sit and reach test, power hop test and multistage fitness test. The data obtained in this study were processed using t-test statistics with a significance level (α) = 5%. The results of research based on research and tests that have been carried out have a significant effect. Judging from the results of calculating the correlation coefficient of the influence and contribution of the old and new norms, namely: for male athletes, the value of R = correlation coefficient is equal to 0.720, while the magnitude of the contribution of the new norm to the old norm is shown by the R Square value of 0.518, which is 51.8%. Whereas for female athletes, the results obtained are R = correlation coefficient of 0.921, which means that the influence is large, while the contribution of the new norm to the old norm is shown by the R Square value of 0.849, which is 84.9%. So it can be concluded that there is an effectiveness of the instruments and norms for testing the physical ability of athletes aged 13-18 years in East Nusa Tenggara Province.